Manajemen Bedah Prolaps Membran Niktitan pada Anjing Beagle di DNA Animal Clinic Bogor: Surgical Management of Niktitan Membrane Prolapse in Beagle Dog at DNA Animal Clinic Bogor - Utomo, Erina Bidari; Lesmana, M. Arfan; Rickyawan, Nofan; Airlangga, Gegana Wimaldy; Waspada, Soenarti D. (Veterinary Biomedical and Clinical Journal, 2022)
An 11-year-old female Beagle dog weighing 18 Kg was brought to the clinic with redness discoloration in her right eye, a cherry like lump, and ocular discharge. Based on the clinical signs, the diagnosis was a prolaps of the nictitating membrane or “Cherry Eye” with a fausta prognosis. The treatment was a surgery using the Morgan Pocket method to maintain the mobility of the nictitating membrane and lymphoid tissue. The postoperative therapy given was the anti-inflammatory drug meloxicam 0.2 mg/kg once a day orally and gentamicin eye ointment (Genoint 0.3% Eye Oint) topically twice a day. Five days after the surgery and treatment, the dog's eyes had improved, and there was no lump observable.